Pelaksanaan Perjanjian Kredit Dengan Jaminan Tanah Di PT. Bank Rakyat Indonesia (Persero), Tbk, Kantor Cabang Karanganyar - Drajat Satrio Husodo; Noor Saptanti (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2024)
The provision of credit facilities in its development will always require collateral. This is due to the necessity of the Law, as well as for the security of the granting of credit, in the sense that the receivables from the bank will be guaranteed by the existence of collateral. Credit more often accepts collateral objects in the form of immovable objects, one of which is land rights because it is easy and certain in its execution. The purpose of this study was to determine the procedure for realizing credit with land collateral at BRI Karanganyar Branch Office, BRI Karanganyar Branch Office's actions against loans that fall into the doubtful category, and how to resolve if the credit in the doubtful category decreases in quality to the bad credit category. The results of this study are the procedure for realizing credit with land collateral at BRI Karanganyar Branch Office.